Korelasi antara Spiritual Intelligence dengan Kemampuan Self-Management Pasien Tuberkulosis Paru - Soleh, Madnur; Restuning Prihati, Dyah; Nur Aini, Dwi (Universitas Duta Bangsa Surakarta, 2025)
Introduction: Spiritual intelligence refers to a belief in God that helps individuals develop abilities by applying spiritual values in adapting to challenges and making appropriate decisions. Effective self-management in tuberculosis patients is essential to prevent drug resistance, improve recovery outcomes, and control the spread of the disease. Objective: This study aims to analyze the relationship between spiritual intelligence and self-management in patients with pulmonary tuberculosis. Method: This quantitative study used a cross-sectional approach with 46 respondents. The research was conducted at the Lung Polyclinic of Batang Hospital over the course of one month. The instruments used were the Daily Spiritual Experience Scale (DSES) questionnaire and a pulmonary tuberculosis self-management questionnaire. Results: The Spearman rank test showed a positive and significant correlation between spiritual intelligence and self-management, with a p-value of 0.000 (p < 0.05) and a correlation coefficient (rho) of 0.678. This is categorized as a strong relationship, indicating that higher spiritual intelligence is associated with better self-management abilities. Conclusion: There is a positive and significant relationship between spiritual intelligence and self-management in patients with pulmonary tuberculosis. These findings support the development of integrated educational interventions that incorporate spiritual aspects to enhance self-management.